Laparoscopic evaluation of pelvic organ in case of subfertility - Ahmed, Polly; Chowdhury, T. A.; Mahmud, Kaniz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Globally subfertility affects 10-15% of couple. All these people need proper evaluation and treatment. Now a days laparoscopy considered as a gold standard procedure for evaluation of pelvic organ. The aim of this study was to find out the different causes of female factor infertility with the help of laparoscopy. Methods: This retrospective study was conducted in infertility clinic of BIRDEM hospital, Dhaka, Bangladesh during the period of May, 2007 to October 2007. The study group comprised 100 cases of infertile patients. Results: In this study, among 100 patients 68% had primary and 32% had secondary infertility. In laparoscopy majority (55.0%) had normal ovary, 20.0% had cystic change with thick capsule in right ovary and 22% had in left ovary, 7.0% had endometriosis, 8.0% had adhesion, 10.0% had simple cyst in right ovary and 8% had in left ovary and rest could not be visualized. 79.4% right and 77.9% left fallopian tube patent in primary subfertility cases and 56.3% right and 59.4% left tube normal in secondary subfertility cases. Both fallopian tube patent in 62%, unilateral block 21% and bilateral block in 17% cases in this study peritoneum was normal in 78% cases, 8% cases there was endometriosis and 14% cases there was adhesion of fallopian tube with the ovary, adhesion of uterus with intestine and also with bladder. Conclusions: Laparoscopy is an important tool for diagnosing anatomical and pathological abnormalities of pelvic organ which has a major role in subfertility management.